Pengaruh Model Pembelajaran Kooperatif Learning Berbantu Media Digital Terhadap Kemampuan Menyusun Laporan Keuangan Siswa SMK Palembang - Aini, Nurul; Gunawan, Hendri; Hodsay, Zahruddin (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the effect of a cooperative learning model assisted by digital media on students’ ability to prepare financial statements. The background of this research is the low level of students’ understanding in preparing financial statements caused by conventional, teacher-centered learning and limited use of digital media. The objective of this study is to analyze whether cooperative learning assisted by digital media can improve students’ financial statement preparation skills. This research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The research subjects were eleventh-grade accounting students at a vocational high school in Palembang. Data were collected through tests, observation, and documentation, and analyzed using descriptive statistics and inferential analysis. The results indicate that students in the experimental group showed higher improvement in mean scores and learning mastery compared to those in the control group. Although the statistical test did not show a significant difference, descriptive data and learning process observations reveal a positive practical impact of cooperative learning assisted by digital media. These findings suggest that the cooperative learning model supported by digital media is a relevant and effective approach for enhancing financial statement preparation skills in vocational accounting education.